Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.3 - Fractional Exponents - Problem Set 11.3 - Page 489: 59



Work Step by Step

We will use the rule $a^{n}a^{m}=a^{n+m}$ in the solution. Therefore, $(2y^{\frac{2}{3}})(y^{-\frac{1}{4}})$ $=(2\times y^{\frac{2}{3}})(1\times y^{-\frac{1}{4}})$ $=(2\times1)\times(y^{\frac{2}{3}}\times y^{-\frac{1}{4}})$ $=(2)(y^{\frac{2}{3}-\frac{1}{4}})$ $=(2)(y^{\frac{2(4)-3}{12}})$ $=2y^{\frac{5}{12}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.